Seleksi Pemilihan Staff Account Receivable dengan Penerapan Sistem Pendukung Keputusan Kombinasi Metode WASPAS dan ROC - Naufal Rifqi; Agus Iskandar (Journal of Computer System and Informatics (JoSYC), 2023)
Appropriate Account Receivable staff must be qualified, have skills, and exhibit traits that are suitable for the duties and responsibilities associated with receivables management. Errors in staff selection can potentially create problems in the management of receivables, result in delays in the collection of funds, and pose a greater risk of loss to the company. Therefore, the selection and selection of qualified Account Receivable Staff is a very key factor in achieving optimal financial performance. Selection in the selection of Account Receivable staff has several criteria, namely Education, Experience, Technical Skills, Communication Skills and Negotiation Skills. In the midst of an increasingly complicated business environment and intense competition, the use of decision support systems (SPK) is becoming more relevant to assist in the optimal employee selection process, given the importance of objectivity and accuracy in the selection process by applying the ROC (Rank Order Centroid) and WASPAS (Weighted Aggregated Sum Product Assesement) methods which are utilized to provide weight values to the selection criteria, while WASPAS is used to verify the results of the selection decision. So that the best Account Receivable Staff selected is alternative A5 with the highest value of 3.8354 as the first rank.